Strategi Pengembangan Desa Wisata Tabek untuk Peningkatan Ekonomi Lokal di Nagari Talang Babungo Kecamatan Hiliran Gumanti - Bundo, Mayang; Muslim, Mulyadi (Universitas Negeri Makassar, 2024)
Tourism has an important role in a sustainable national economy by encouraging the growth of the service sector, absorbing labor through job creation, encouraging regional development, and supporting economic inclusiveness. In its development, tourism can be derived in the form of community-based tourism. The Nagari Talang Babungo area is a potential tourist village owned by Hiliran Gumanti District, Solok Regency. This Nagari has a wide and beautiful landscape so that it can be used as a tourist attraction and share various agro commodities. This research aims to describe the potential and strategy for developing tourist villages in Nagari Talang Babungo, which is the government center of Hiliran Gumanti District. The collection process was carried out by means of observation, interviews and documentation. The analytical method used is guided by the provisions of qualitative methodology in general, such as reduction, data presentation, verification and data triangulation. The results of data analysis are presented in this article in the form of a narrative or table in accordance with the systematics of writing the article. From the results of the SWOT analysis carried out, the tourism village development strategy carried out is developing tourist attractions, increasing the adequacy of facilities and infrastructure, increasing accessibility for visitors, empowering the community, establishing cooperation in development and empowerment in marketing.